PROFIL TINDAKAN INSTRUKSIONAL GURU DALAM STRATEGI PENGELOLAAN KELAS DALAM MENINGKATKAN KEAKTIFAN DAN DISIPLIN BELAJAR SISWA - Erika Isseli Yukepti; Ahmad Agung Yuwono; Juhana, Juhana (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study addresses persistent challenges in elementary classroom practices, particularly low student activeness and weak learning discipline that hinder effective instructional processes. These issues are closely related to how teachers design and implement instructional actions within classroom management strategies. The study aimed to analyze the profile of teachers’ instructional actions in planning learning activities, managing classroom conditions, regulating student behavior, and fostering student participation to enhance activeness and learning discipline. A qualitative descriptive approach was employed, involving classroom teachers at SD Negeri Kenaran 3. Data were collected through classroom observations, in-depth interviews, and document analysis of lesson plans and instructional records. Data analysis was conducted through systematic stages of data reduction, data display, and conclusion drawing, with credibility ensured through triangulation of sources and techniques. The findings reveal that teachers’ instructional actions were generally well-structured at the planning stage, particularly in organizing learning objectives and instructional activities. Classroom management strategies emphasizing clear rules, positive reinforcement, and preventive approaches contributed to improved learning discipline. Moreover, interactive instructional actions, such as questioning strategies, group discussions, and varied learning activities, played a significant role in increasing student activeness. However, the study also identified constraints related to time limitations and differences in student characteristics that affected the consistency of implementation. Overall, effective instructional actions integrated with purposeful classroom management strategies were shown to support the development of a more active and disciplined learning environment. The results provide practical implications for teachers and schools in strengthening classroom-based instructional practices.